Neural Processing Mechanism of Mental Calculation Based on Cerebral Oscillatory Changes: A Comparison Between Abacus Experts and Novices - Belkacem, Abdelkader Nasreddine; Kiso, Kanako; Uokawa, Etsuko; Goto, Tetsu; Yorifuji, Shiro; Hirata, Masayuki (Frontiers in Human Neuroscience, 2020)
Background: Abacus experts can mentally perform fast mathematical operations using multi-digit numbers. The temporal dynamics of abacus mental calculations are still unknown, although some behavioural and neuroimaging studies have suggested visuospatial and visuomotor neural processes during abacus mental calculations. Therefore, this study aims to clarify the significant similarities and differences between expert and novice abacus users by investigating calculation-induced neuromagnetic responses based on cerebral oscillatory changes. Methods: Twelve to 13 healthy abacus experts and 17 non-experts participated in two experimental paradigms using non-invasive neuromagnetic measurements. In both experiments 1 and 2, the spatial distributions of oscillatory changes present during mental calculations and the time and spectrotemporal profiles during addition and multiplication tasks were calculated. MEG data were analysed using synthetic aperture magnetometry (SAM) with an adaptive beamformer to calculate the group averages of the spatial distribution of oscillatory changes and their temporal frequency profiles in source level analyses. Results: Using group averages of the spatial distributions of oscillatory changes, we observed some common brain activities in both right-handed abacus experts and non-experts. In the non-experts, we detected activity changes in the right dorsolateral prefrontal cortex (DLPFC) and bilateral intraparietal sulcus (IPS), whereas in experts, we mainly detected changes in the bilateral parieto-occipital sulcus (POS), right inferior frontal gyrus (IFG), and left sensorimotor area. Based on these findings, we proposed calculation processing models for both abacus experts and non-experts. Conclusion: The proposed model of calculation processing in abacus experts and novices revealed that the novices could perform logical calculations using numerical processing originating in the left IPS. In contrast, abacus experts utilise spatial processing using a memorised, imaginary abacus, and this processing is distributed over the two hemispheres.